Detect and avoid an ultra-wideband - Mishra, Shridhar Mubaraq
Cognitive radios have been advanced as a technology for the opportunistic use of underutilized spectrum wherein secondary devices sense the presence of the primary user and use the spectrum only if it is deemed empty. Spectral cognition of this form can also be used by regulators to facilitate the dynamic coexistence of different service types. An example of this is the operation of ultra-wideband devices in WiMAX bands: UWB devices must detect and avoid WiMAX devices in certain regulatory domains. In this article we start by discussing various options for detection and avoidance. We then describe the obstacles faced in achieving robust detection and avoidance with an on-chip implementation of basic DAA functionality. Finally, we present measurement results for operation of a single UWB device with a WiMAX system. This interaction also highlights the problem of dealing with listen before speak primaries where secondary transmission could interfere by blocking the primary's access to the medium.
Keywords: WiMAX bands; WiMAX devices; Cognitive radios; Spectral cognition; Ultra-wideband devices; Ultra-wideband/WiMAX coexistence mechanism